Occasional Combinatorial Lexicology as an Area of Study of Occasional Collocations - M. V. Vlavatskaya; A. V. Korshunova (Научный диалог, 2018)
The article is devoted to occasional combinatorial lexicology as a separate area of combinatorial linguistics, more precisely, to lexicology studying occasional collocations, or atypical, individually authored and non-reproducible word combinations created through deliberate violation of lexico-semantic compatibility for performing certain functionally expressive tasks within a specific text. Particular attention is paid to the fact that the authors create and include occasional collocations for various purposes: first, to express an unconventional attitude to the object or subject described, secondly, to give it its own characteristic, thirdly, to put a certain emphasis on any part of the narration, etc. The technique of the functional-semantic analysis of occasional collocations as the basic, complex method of investigation is presented in the article, and features of this type of collocations are revealed. The authors believe that the allocation of occasional combinatorial lexicology contributes to the development and improvement of combinatorial science and the lexicological branch, provides scientifically substantiated interpretation and description of special lexical units - occasional collocations.